The Progressive Approach to EMDR Group Therapy for Complex Trauma and Dissociation: A Case-Control Study - Gonzalez-Vazquez, Ana I.; Rodriguez-Lago, Lucía; Seoane-Pillado, Maria T.; Fernández, Isabel; García-Guerrero, Francisca; Santed-Germán, Miguel A. (Frontiers in Psychology, 2018)
Eye Movement Desensitization and Reprocessing is a psychotherapeutic approach with recognized efficiency in treating Posttraumatic Stress Disorder (PTSD), which is being used and studied in other psychiatric diagnoses partially based on adverse and traumatic life experiences. Nevertheless, there is not enough empirical evidence at the moment to support its usefulness in a diagnosis other than PTSD. It is commonly accepted that the use of EMDR in severely traumatized patients requires an extended stabilization phase. Some authors have proposed integrating both the theory of structural dissociation of the personality and the adaptive information processing model guiding EMDR therapy. One of these proposals is the Progressive Approach. Some of these EMDR procedures will be evaluated in a group therapy format, integrating them along with emotional regulation, dissociation, and trauma-oriented psychoeducational interventions. Patients presenting a history of severe traumatization, mostly early severe and interpersonal trauma, combined with additional significant traumatizing events in adulthood were included. In order to discriminate the specific effect of EMDR procedures, two types of groups were compared: TAU (treatment as usual: psychoeducational intervention only) vs TAU+EMDR (the same psychoeducational intervention plus EMDR specific procedures.) In pre-post comparison, more variables presented positive changes in the group including EMDR procedures. In the TAU+EMDR group, 4 of the 5 measured variables presented significant and positive changes: general health (GHQ), general satisfaction (Schwartz), subjective well-being, and therapy session usefulness assessment. On the contrary, only 2 of the 5 variables in the TAU group showed statistically significant changes: general health (GHQ), and general satisfaction (Schwartz). Regarding post-test inter-group comparison, improvement in subjective well-being was related to belonging to the group that included EMDR procedures, with differences between TAU and TAU+EMDR groups being statistically significant (2(1)=14.226; p<0.0001). In the TAU+EMDR group there was not one patient who got worse or did not improve; 100% experienced some improvement. In the TAU group, 70.6% referred some improvement, and 29.4% said to have gotten worse or not improved.